Effects of schema therapy and schema-focused mindfulness therapy on conflict resolution of Iranian women in Malaysia - Nooroney, Nooshin; Wan Jaafar, Wan Marzuki; Hassan, Siti Aishah; Mohd Noah, Sidek (Human Resource Management Academic Research Society, 2017)
This study aimed to investigate the effectiveness of schema therapy and schema-focused mindfulness therapy on conflict resolution among Iranian married women who lived in Malaysia during ?2015-2016. The qualified participants included 96 women who were assigned randomly into three groups, i.e. two experimental groups and a control group. The first experimental group received schema therapy and the second group received schema-focused mindfulness therapy while the control group did not receive any treatment. The treatment sessions lasted nearly three months using conflict resolution subscale from the ENRICH questionnaire, a demographic questionnaire and Young's schema questionnaire as the instruments. Two-way repeated measures ANOVA was also applied to analyze the results. The findings of the study revealed that schema therapy and schema-focused mindfulness therapy had a significant effect on conflict resolution of Iranian women in Malaysia. Moreover, the findings showed more improvement for schema-focused mindfulness therapy group at two months follow-up.